Carik-carik bulu ayam : kisah runding bahasa dunia Melayu - Asmah Haji Omar , 1940- (Siri penerbitan Mabbim, 2010)
Historical development of Mabbim, Brunei-Indonesia-Malaysia Language Council, and its role on development, standardization, and harmonization of Malay languages used in Brunei, Indonesia, and Malaysia